Smart Contract Management in Resource Sharing Agreements - Pavitra, A. Rehash Rushmi; Radha, R.; Kumar, R. Satheesh; MuhsnHasan, Montater; kizi, Yuldasheva Maftuna Mamurjon; Sharma, Nishtha (Indian Journal of Information Sources and Services, 2026)
The management of resource sharing agreements is being transformed by the introduction of smart contracts, which, alongside decentralized technologies, provide smoother automation, transparency, and trust amongst different parties. This research examines the role that smart contract management systems play in the design, implementation, and control of resource-sharing agreements in the fields of energy, telecommunications, transportation, and digital services. Conventional contract-based practices are plagued by inefficiencies, potential errors, and delays, which smart contracts aim to address by encoding agreement terms into self-executing code stored within blockchain systems. The study examines key architectural building blocks, consensus models, and security elements, focusing on the real-time execution of automated validation, updates, dispute resolution, and contract performance. Practical applications are presented through case studies on decentralized energy markets, bandwidth leasing, and co-utilization of assets. Other concerns are the lack of interconnected systems, enforcement, and private legal structures. The research develops a smart contract lifecycle management model that regulates contracting processes to help organizations develop adequate, compliant, and collaborative resource distribution solutions designed to be scalable. The economic model of spending changes due to the ability of smart contracts, utilizing Blockchain, to share resources, thereby reducing administrative expenses and establishing more resilient mechanisms of dependence in the future.